Consumption of the Epidermis: A Suggested Precursor of Ulceration Associated With Increased Proliferation of Melanoma Cells. (November 2015) - Bønnelykke-Behrndtz, Louise M.; Schmidt, Henrik; Damsgaard, Tine E.; Christensen, Ib Jarle; Bastholt, Lars; Møller, Holger J.; Nørgaard, Peter; Steiniche, Torben
Abstract : Abstract: It has recently been demonstrated that the extent of ulceration and the presence of epidermal involvement that theoretically precede ulceration (consumption of epidermis, COE) or seen subsequent to inflammation (reactive epidermal hyperplasia or re-epithelialization) allowed better prognostic stratification of ulcerated melanoma. Understanding why these histopathologic markers have prognostic potential is important, not least because accurate consensual assessment of ulceration lies at the root of proper staging and clinical management. The authors therefore performed immunohistochemical analyses of tumor cell proliferation (Melan-A/Ki67) and infiltration of inflammatory cells (CD66b + neutrophils and CD163 + macrophages) to better understand the biology of the epidermal changes described. Tumors with a COE configuration showed 37% (95% CI: 4–54, P = 0.0046) increased tumor cell proliferation compared with tumors of normal epidermal configuration. COE is therefore suggested a precursor of ulceration associated with increased proliferation of melanoma cells. There was no observed correlation between COE and an increased inflammatory response (CD163 + macrophages or CD66b + neutrophils), which supports that the proliferation drive is noninflammatory. In contrast, the presence of re-epithelialization and/or reactive epidermal hyperplasia demonstrated an 18% (95% CI: 6–53, P = 0.0021) increased density of neutrophils compared with tumor with no evidence of these possibly prolonged late-stage or resolved ulcerations. These results further support the relevance of including these epidermal changes into the definition of ulceration and to define ulceration of a primary melanoma as loss of epidermis with evidence of a host response (infiltration of neutrophils or fibrin deposition) and thinning, effacement, or reactive hyperplasia of the surrounding epidermis .